Blind spots in ecosystem services research and challenges for implementation - Lautenbach, Sven; Mupepele, Anne-Christine; Dormann, Carsten F.; Lee, Heera; Seppelt, Ralf; Teeffelen, Astrid van; Verhagen, Willem H.; Volk, Martin (Regional environmental change, 2019)
Ecosystem service research is high on the policy agenda. Strategies to synthesize individual success stories and derive generalized results to provide guidance for policymakers and stakeholder is central to many science-policy initiatives, such as Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services and The Economics of Ecosystems and Biodiversity. However, generalization requires the documentation of basic information on methods and results of case studies, which might not be present throughout all case studies. We used a quantitative review based on a random sample of studies published in the ISI Web of Knowledge between 1996 and 2016 to identify blind spots in ecosystem service research that might hinder the generalization. We structured our analysis along critical questions about five facets that characterize the holistic ideal of ecosystem services research: (i) social-ecological validity of ecosystem data and models, (ii) consideration of trade-offs between ecosystem services, (iii) recognition of off-site effects, (iv) comprehensive and shrewd involv ement of stakeholders, and (v) relevance and usability of study results for the operationalization of the ecosystem service concept in practice. Results show that these facets were not addressed by the majority of case studies including more recent studies. Clusters of ecosystem services studied together were prone to different blind spots. To effectively operationalize the concept of ecosystem services, the blind spots need to be addressed by upcoming studies. A list of critical questions is provided to raise the awareness of the blind spots both for synthesis of existing knowledge and for future research agendas.
Gesehen am 25.03.2020